Mycobacterium tuberculosis‐associated synthetic mycolates differentially exert immune stimulatory adjuvant activity. Issue 9 (29th July 2016) - Smet, Muriel; Pollard, Charlotte; De Beuckelaer, Ans; Van Hoecke, Lien; Vander Beken, Seppe; De Koker, Stefaan; Al Dulayymi, Juma'a R.; Huygen, Kris; Verschoor, Jan; Baird, Mark S.; Grooten, Johan
Abstract : Mycolic acids are fatty acids present in the cell wall of Mycobacterium tuberculosis . In this study, we show that mycolic acids display differential immune stimulatory adjuvant activity dependent on their stereochemistry and functional groups. Mycolic acid immunization results in the induction of a Th1, Th17, and cytotoxic T‐cell immune response. Abstract : Mycolic acids (MAs) are highly hydrophobic long‐chain α‐alkyl β‐hydroxy fatty acids present in the cell wall of Mycobacterium tuberculosis ( Mtb ) as a complex mixture of molecules with a common general structure but with variable functional groups in the meromycolate chain. In this study, we addressed the relationship between the MA molecular structure and their contribution to the development of T‐cell immune responses. Hereto, we used the model antigen ovalbumin and single synthetic MAs, differing in oxygenation class and cis versus trans proximal cyclopropane configuration, as immune stimulatory agents. Subcutaneous delivery of liposome‐formulated MAs with a proximal cis cyclopropane elicited antigen‐specific Th1 and cytotoxic T‐cell immune responses, whereas intratracheal immunization elicited pulmonary Th17 responses. These immune stimulatory activities depended not only on the cis versus trans proximal cyclopropane configuration but also on the MA oxygenation class. Our study thus shows that both the presence and nature of the functional groups in the meromycolate chain affect the immune stimulatory adjuvant activity of Mtb mycolates and suggests that Mtb bacilli may impact on the host protective immune response by modulating the cis versus trans stereochemistry of its mycolates as well as by altering the oxygenation class of the meromycolate functional group.